The Objective Conditions for the Formation of Innovative Management of Enterprise Development: the Scientific-Historical Basis for Overcoming the Consequences of Crises - Prokhorova Viktoriia V.; Davydova Oksana Yu. (Bìznes Inform, 2018)
The article is aimed at substantiating the objective conditions of formation of innovative management of enterprises development on the basis of the scientific-historical aspect of overcoming the consequences of crises. An analysis of scientific literary sources was carried out, and a chronology of the largest world economic crises was formed, ways of their overcoming were explored, the main world developments on the theory of crises were considered. It is determined that each stage had its own regularities, its level of potential development, and its attracted resources. In accordance with the stages of development new requirements were put forward, innovative orientation were created, new knowledge, practices and skills were required. On the basis of the conducted analysis of scientific literature, the data on development and formation of scientific thought in accordance with a periodization of crises have been formed. The scientific-historical basis of formation of innovative management of development of enterprises is elaborated, which provides an opportunity to prove, that each innovation realizing the great invention, creates preconditions for the formation of system of innovative management of the development of new generations.